Effects of black seed (Nigella Sativa) on type 2 cytokines gene expression and mucus production in the airways of asthmatic mice - Azimi, Ebrahim; Athari, Seyyede Masoume; Afshari, Faride; Eftekhari, Asie; Athari, Seyyed Shamsadin (Archives of Medical Laboratory Sciences, 2019)
Background: Black Seed (BS) is used in traditional medicine as a therapy for a variety of diseases including allergic asthma. Materials and Methods: In the present study, anti-inflammatory and immunomodulatory effects of BS on cytokine gene expression, lung airway eosinophilia and goblet cell hyperplasia were examined in a mouse mice model of allergic asthma. Groups of 6-week-old female BALB/c mice were sensitized by intraperitoneal injections of OVA plus alum on days 1 and 14. On days 24, 26, 28 and 30, the mice were exposed to OVA in saline for 30 min with nebulizer. Similar experiments were conducted with mice receiving saline as a negative control. Results: The mouse allergic asthma model received BS by food on days 23, 25, 27 and 29. Then, the percentage of inflammatory cells as well as mRNA expression levels of interleukin (IL)-4, IL-5, IL-13 and mucin (MUC5a) genes were survived in Broncho-alveolar lavage fluid (BALF). Furthermore, we attempted to examine histopathological examination of the lung. Mice receiving BS showed a significant decrease in the number of eosinophils, and a potential inhibitory effect on mRNA expression levels of Th2-driven immune response cytokines and mucin, resulting in decreased production of interleukin and mucin in allergic asthma. Conclusion: Our findings suggested that BS has an anti-inflammatory and immunomodulatory effect during the allergic response in the lung, and can be a promising treatment for allergic asthma in humans.